Fate of adipocyte progenitors during adipogenesis in mice fed a high-fat diet - Muhammad Bilal; Allah Nawaz; Tomonobu Kado; Muhammad Rahil Aslam; Yoshiko Igarashi; Ayumi Nishimura; Yoshiyuki Watanabe; Takahide Kuwano; Jianhui Liu; Hiroyuki Miwa; Takumi Era; Koichi Ikuta; et al. (Elsevier, 2021)
Objective: Expansion of adipose tissue during obesity through the recruitment of newly generated adipocytes (hyperplasia) is metabolically healthy, whereas that through the enlargement of pre-existing adipocytes (hypertrophy) leads to metabolic complications. Accumulating evidence from genetic fate mapping studies suggests that in animal models receiving a high-fat diet (HFD), only adipocyte progenitors (APs) in gonadal white adipose tissue (gWAT) have proliferative potential. However, the proliferative potential and differentiating capacity of APs in the inguinal WAT (iWAT) of male mice remains controversial. The objective of this study was to investigate the proliferative and adipogenic potential of APs in the iWAT of HFD-fed male mice. Methods: We generated PDGFRα-GFP-Cre-ERT2/tdTomato (KI/td) mice and traced PDGFRα-positive APs in male mice fed HFD for 8 weeks. We performed a comprehensive phenotypic analysis, including the histology, immunohistochemistry, flow cytometry, and gene expression analysis, of KI/td mice fed HFD. Results: Contrary to the findings of others, we found an increased number of newly generated tdTomato+ adipocytes in the iWAT of male mice, which was smaller than that observed in the gWAT. We found that in male mice, the iWAT has more proliferating tdTomato+ APs than the gWAT. We also found that tdTomato+ APs showed a higher expression of Dpp4 and Pi16 than tdTomato− APs, and the expression of these genes was significantly higher in the iWAT than in the gWAT of mice fed HFD for 8 weeks. Collectively, our results reveal that HFD feeding induces the proliferation of tdTomato+ APs in the iWAT of male mice. Conclusion: In male mice, compared with gWAT, iWAT undergoes hyperplasia in response to 8 weeks of HFD feeding through the recruitment of newly generated adipocytes due to an abundance of APs with a high potential for proliferation and differentiation.